Starkad og Egil Skallagrimsson som Odinshelte - Lindhart Boll, Jens Kristian (Religionsvidenskabeligt tidsskrift, 1986)
When reading old Norse epics, scholars have been astonished that the iron-age warrior Starkad and the Icelandic farmer Egil Skallagrimsson belong to the group of Norse heroes. The two of them constantly violate the ethics of the hero through ferociousness and greed. However, their behavior might be understood if related to the dual aspects of the chief Norse god Odin: just as the ordinary heroes, called Odin-heroes, with the god Balder as the prototype, reflected the “light” side of Odin’s aspects as ruler, warrior and sage, Starkad and Egil seem to reflect hos “darker” aspects as sorcerer and the god of the slain. Such a relationship makes the behavior of Starkad and Egil more understandable. The existence of Odin-heroes reflecting the somber aspects of the god may even shed an interesting side-light on the bard as literary figure in Norse epics, where the bards often seem unable to adapt to ordinary life but instead disrupt the harmony and cause sanguinary conflict by their actions.